Dynamic Provisioning - Saurina, Jesus (World Bank, Washington, DC, 2012)
Dynamic loan loss provisions can help deal with procyclicality in banking. By allowing earlier detection and coverage of credit losses in loan portfolios, they enable banks to build up a buffer in good times that can be used in bad times. Their anticyclical nature enhances the resilience of both individual banks and the banking system as a whole. While there is no guarantee that they will be enough to cope with all the credit losses of a downturn, dynamic provisions have proved useful in Spain during the current financial crisis. They could be an important prudential tool for emerging economies, where banks dominate financial intermediation.